Study of kinematics of spatial 5R mechanism with 4 cyclic motion - R. T. Islamov; F. F. Khabibullin; M. R. Faizov (Омский научный вестник)
This article presents Bennett's five-bar spatial mechanism. For interest, we will define the kinematic parameters of the mechanism. The obtained parameters displayed on the graphs of the dependences of the rotation of the input link to the output. Additionally, for an accurate calculation, an additional ghostly angle of the mechanism is taken into account. Additional link ratios specified.